Optimizing Basketball Team Performance through The Application of Sports Psychology Management and Mental Coaching - Encep Farlan Sutarza; Lalu Hulfian (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
Team performance in sports, especially basketball, is not only determined by physical ability and tactics, but also by psychological factors. The pressure of competition, team dynamics, and individual demands require a comprehensive approach that integrates aspects of sports psychology. This study aims to investigate the impact of applying sports psychology management and mental coaching on improving the performance of basketball teams in Bandung. This study uses a quantitative approach with an experimental design. The research subjects consisted of two youth basketball teams in Bandung, which acted as the experimental and control groups, respectively. The experimental group was given an intervention in the form of a 12-week mental training program, which included visualization techniques, self-talk, stress management, and team cohesion enhancement. Team performance was measured using a series of indicators, including winning percentage, individual statistics (e.g., field goal percentage and assist-to-turnover ratio), and psychological evaluations (e.g., pre-game anxiety levels). Data analysis results showed a significant improvement in the performance of the experimental team after the intervention, compared to the control group. This improvement was seen in the winning percentage, team cohesion, and decreased anxiety levels. This study proves that sports psychology management and mental coaching programs are effective in optimizing basketball team performance.